Changing provision and use of neighbourhood public space in Nepal’s Kathmandu Valley - Chitrakar, Rajjan Man; Baker, Douglas C.; Guaralda, Mirko (Journal of Architecture and Urbanism, 2017)
Modern cities have witnessed a significant level of transformation of urban environments, in which the urban neighbourhoods of recent origin have also changed. This paper explores the transformation of public space in contemporary urban neighbourhoods of the Kathmandu Valley in Nepal. It examines the changing provision and use of public space through a case study of three recent neighbourhoods using observations and interviews. The study identifies fundamental differences in the development of public space, suggesting that public spaces are no longer the central elements of new neighbourhoods. Further changes with the provision of public space include the existing spatial configuration of open spaces, the loss of social quality of neighbourhood streets and the rise of alternative public venues. The changing provision of public space has influenced the use with the shifting locations of public activities. There is a growing tendency to use the streets as a public space along with other privately owned public spaces. While a large portion of public space remains underutilised or has been put into an inappropriate use, some new uses of public spaces are also noticed in the changing context.